Architectural spatial design strategies for summer microclimate control in buildings: a comparative case study of Chinese vernacular and modern houses - Du, Xiaoyu; Bokel, Regina; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2019)
The objective of this paper is to clarify the spatial design strategies used to control the microclimate of a Chinese vernacular house in summer by comparing the building with modern Chinese rural houses and presenting ideas for contemporary architectural design practice. For this goal the spatial configuration, the spatial boundary conditions, the vegetation in the space and the human activity in the space were analysed for the vernacular house and for modern rural houses. Also, field measurements were conducted to evaluate the summer thermal environment in the vernacular and a modern house. The results show that the vernacular house has a diverse spatial design and a better building microclimate, making it easier to obtain thermal comfort than the modern houses. Therefore, spatial design strategies of Chinese vernacular houses are still of great value to modern house design, especially when the free-running thermal comfort theory is applied.